3D imaging by mass spectrometry: a new frontier - Seeley, Erin H; Caprioli, Richard M (Analytical chemistry (Washington), 2012)
Imaging mass spectrometry can generate three-dimensional volumes showing molecular distributions in an entire organ or animal through registration and stacking of serial tissue sections. Here, we review the current state of 3D imaging mass spectrometry as well as provide insights and perspectives on the process of generating 3D mass spectral data along with a discussion of the process necessary to generate a 3D image volume.